The Qїrghїz Baatïr and the Russian Empire : A Portrait of a Local Intermediary in Russian Central Asia - Akiyama, Tetsu (Islamic Area Studies, 2021)
In The Qїrghїz Baatïr and the Russian Empire Tetsu Akiyama gives a vivid description of the dynamism and dilemmas of empire-building in nomadic Central Asia from the mid-nineteenth to the early twentieth century, through reconstructing the biography of Shabdan Jantay uulu (ca. 1839-1912), a chieftain from the northern Qїrghїz (Kirghiz, Kyrgyz) tribes. Based on the comprehensive study of primary sources stored in the archives of Central Asian countries and Russia, Akiyama explores Shabdan's intermediary role in the Russian Empire's military advance and rule in southern Semirech'e and its surrounding regions. Beyond the commonly held stereotype as a "faithful collaborator" to Russia, he appears here as a flexible and tough leader who strategically faced and dealt with Russian dominance.